Working memory in Music: Main Theoretical Milestones and Some of the Challenges in its Study - Yamaguchi, Vitor Djun [UNESP]; Bortz, Graziela [UNESP] (Universidade Federal de Goias, 2021)
The working memory as a phenomenon provides many debates about human storage capacity, even before the emergence of experimental psychology. This paper will discuss two main theoretical concepts: Baddeley's multifaceted holding mechanism (1986; 2000) and Cowan's embedded-processes model (1988; 2005). We showed their common and complementary elements, bringing a non-hegemony approach, considering that some musical tools remain misunderstood. The pure concept of limit, generally discussed under chunking terms, is a challenge for this investigation, since it is supposed to be a simplifying construct that does not express all influence of previous knowledge. Also, behavioral and neuroimage evidence shows that the storage capacity will range according to each parameter that was seized.
Memória operacional em música: Principais marcos teóricos e alguns dos desafios em seu estudo
Keywords: Musical memory; Working memory